Misuse and interlaboratory test reproducibility of API 20E system. - Holmes, B (1985)
One hundred strains were referred to us for identification because they apparently could not be identified satisfactorily with the API 20E system (appareils et procédés d'identification). The inability to identify 31 strains was due primarily to failure to follow the manufacturer's instructions. Twenty six further strains were found to have been correctly identified by the sender's own API 20E results, so that only the remaining 43 strains definitely fell into the category for which our identification service was intended. Eighteen of the 43 strains not identified by the sender were identified by us using the API 20E system, and several possible reasons are given to explain the differences in these results. The remaining 25 strains either could not be identified by us on the API 20E system or, in the case of 13, they could not be identified by our conventional system and therefore no comparison could be made. The average interlaboratory probability of errors for the API 20E tests was 6.1%.